Efficacy and safety of 5‐hydroxytryptophan on depression and apathy in Parkinson's disease: a preliminary finding. (13th March 2020) - Meloni, M.; Puligheddu, M.; Carta, M.; Cannas, A.; Figorilli, M.; Defazio, G.
Abstract : Background and purpose: Several studies have indicated that altered serotonergic neurotransmission may contribute to non‐motor features commonly associated with Parkinson's disease (PD) such as apathy and depression. 5‐hydroxytryptophan (5‐HTP) is the intermediate metabolite of L‐tryptophan in the production of serotonin. To date, there has been inconsistent research on the use of 5‐HTP in PD. The purpose of this study was to compare the effects of 5‐HTP with those of placebo on apathy and depressive symptoms in patients with PD. Methods: A single‐center, randomized, double‐blind placebo‐controlled cross‐over trial was employed; 25 individuals were subsequently enrolled into the study. Patients received placebo and 50 mg of 5‐HTP daily over a period of 4 weeks. For the assessment of efficacy on depressive and apathy symptoms the Beck Depression Inventory‐II (BDI‐II), Hamilton Depression Rating Scale (HDRS) and Apathy Scale (AS) were respectively administered at screening, baseline and weeks 4, 8, 12 and 16. Primary efficacy outcomes were the comparison of 5‐HTP to placebo in mean change from baseline to weeks 4, 8, 12 and 16 in total score on the AS, BDI‐II and HDRS. Results: Repeated‐measures analysis revealed a significant improvement of depressive symptoms during the 50‐mg 5‐HTP treatment compared with placebo as assessed by the HDRS. No effect of 5‐HTP was seen on apathy symptoms assessed by the AS. Conclusions: This study provides preliminary evidence of clinical benefit of 5‐HTP for treating depressive symptoms in PD. Larger studies with a longer treatment duration are needed to corroborate these early findings.